Evaluation of antimycobacterial activity from marine and freshwater microalgae - Ruiz-Güereca, Duahmet A.; Licea-Navarro, Alexei F.; Sánchez-Saavedra, M. del Pilar (Revista de Biología Marina y Oceanografía, 2019)
Tuberculosis is considered one of the most important epidemiological diseases worldwide. The current treatment for tuberculosis is a combination of antituberculosis drugs for at least 9 months. Nowadays, the search for new pharmacological agents for the treatment of tuberculosis is an urgent endeavor. Microalgae produce a wide variety of molecules that possess biological activities of pharmaceutical interest. Therefore, the objective of this work was to evaluate the antimycobacterial activity of hexane crude extracts of 6 microalgae: Chlamydomonas mexicana, Porphyridium cruentum, Isochrysis galbana, Rhodomonas sp., Aphanocapsa marina, and Nitzschia palea. All of the hexane extracts inhibited at least 90% of the growth of Mycobacterium tuberculosis H37Rv at a concentration of 100 μg ml-1. The hexane crude extract of I. galbana had the highest antimycobacterial activity displaying a percentage inhibition that was equal to that of the antituberculosis drug isoniazid and having a minimum inhibitory concentration of 50 μg ml-1. These findings demonstrate that microalgae are an excellent source for the search of novel antimycobacterial compounds.